Mastitis in Lactating Cows, Camels and Goats in Borana, Southern Ethiopia - Badaso, Ahmed; Amenu, Kebede; Wieland, Barbara; Megersa, Bekele (Journal of Science and Development, 2021)
Mastitis is a complex and multi-factorial disease, the occurrence and severity of which depends on factors related to the animal, the environment and pathogens involved. Mastitis reduces the quality and quantity of milk, and is a disease of great economic and public health importance. A cross-sectional study was conducted to estimate the prevalence of mastitis and identify the associated risk factors in cows, camels and goats in Yabello district of Borana zone, Southern Ethiopia. A total of 980 lactating animals (400 cows, 370 camels and 210 goats) were sampled and examined clinically for mastitis presence. Milk samples were further tested by California Mastitis Test (CMT) to detect subclinical mastitis. The study results revealed that 49.75% of the cows, 35.41% of camels and 24.76% of goats had udder infections. Cows had significantly higher mastitis prevalence than camels and goats. Quarter/halve level prevalence was 24.94% in cows, 12.64% in camels and 15.71% in does while 76 teats (63 in cows and 13 in camels) were found to be blind. Risk factors identified for cows were age above five years (OR=5.75), parity of 3 and above (OR=3.13), early lactation stage (OR=0.49), animals having teat lesions (OR=1.50) and teat affected by ticks (OR=2.3). Similarly, early lactation stages, udder tick infestations and teat lesion were the risk factors for camels. Mastitis prevalence was higher in multifarious goats, does above five years, and those with udder ticks and teat lesions. In conclusion, mastitis was widely prevalent in lactating cows, camels and goats in the pastoral area, where milk is the major staple food. Hence, proper control strategies and awareness of livestock keepers are needed to reduce mastitis prevalence and its negative impacts on milk production in the study area.